Clinical consequences of untreated dental caries according to the pufa index in children from Taquile Island, Puno - Carcausto Cucho, Marily (2022)
Objective: To determine the prevalence of clinical consequences of untreated dental caries according to the pufa index in children between 3 and 7 years of age on the island of Taquile Puno. Methods: The study was a descriptive, observational and cross-sectional design with a non-probabilistic sample, where 147 children from 3 to 7 years of age of both sexes were evaluated. Clinical oral examinations were performed using the pufa index. After tabulation, the  data were analyzed with the chi-square test with a significance of 0.05. Results: The prevalence of pulp disease in teeth with untreated caries according to the pufa index in children aged 3 to 7 years in Taquile-Puno was 36%; of which 17% were female and 19% male (p<0.05). The highest prevalence was at 5 years of age (p<0.05), and the most frequent pathology was pulpitis with 61%. The most affected tooth according to the pufa index was 8.4 (16%). The most affected arch was the lower arch with 55% (p<0.05). Conclusions: The prevalence of pulp disease in teeth with untreated caries according to the pufa index in children aged 3 to 7 years in Taquile-Puno was 36%, with the highest prevalence at five years of age. The main condition was pulpitis and the tooth with the highest prevalence was 8.4.